Antibiotic Susceptibility of Streptococcus Pyogenes Isolated from Respiratory Tract Infections in Dakar, Senegal. (January 2013) - Camara, Makhtar; Dieng, Assane; Boye, Cheikh Saad Bouh
Group A Streptococcus (GAS) is one of the major causes of respiratory tract infections. The objectives of this study were to identify isolates of S. pyogenes obtained from respiratory tract infections, and to assess their susceptibility to several antibiotics. A total of 40 strains were isolated and their susceptibility to 17 antibiotics was tested using a standard disk diffusion method. The minimum inhibitory concentrations (MICs) were determined using the E-test. All isolates were sensitive to β-lactam antibiotics including penicillin, amoxicillin, and cephalosporins. Macrolides remain active with the exception of spiramycin, which showed reduced susceptibility. Out of the 40 isolates, 100% of the isolates were resistant to tetracycline. Interestingly, isolates were sensitive to chloramphenicol, teicoplanin, vancomycine, and levofloxacin, providing potential alternative choices of treatment against infections with S. pyogenes.